Determination of service charge and sinking fund by management corporation / Abd Latif A Talib - A Talib, Abd Latif (2010)
The purpose of this research is to get the information about determination of service charge and sinking fund by management corporation. Information about how the determination of service charge and sinking fund is important because service charge and sinking is the main components which can give impact to the successful of the strata residential management. First objective is to make research on how the determination of service charge and sinking fund by management corporation. Second objective is to get the information about what items or elements included in determination of service charge and sinking fund by management corporation. Data collection is by interview session with the management team of four strata residential scheme in the research area. Data is analyzed by interview analysis method. Findings show that all the strata residential management team use same method in determination of service charge which is by using formula of all contractors' service plus other services and divided by parcel unit area. The recommendation for improvement is to add the detail about item included in determination of service charge in the payment invoice to prevent the doubt from owners about what they pay for service charge.